Bertolt Brecht's Schweyk im zweiten weltkrieg - Hewson, Thomas Massy Lindsay (My University, 1974)
This study offers a detailed analysis of the main character of Bertolt Brecht's play Schweyk im zweiten Weltkrieg. The play has, to a large extent, been neglected, criticised and generally regarded as a second-rate Hork. One of the objects of this study is to destroy that view. Schweyk is seen as conforming to a typically Brechtian pattern, in that he is basically a character made up of two conflicting, socially conditioned sides. This study attempts to bring these two sides into perspective, thus showing Schweyk in his true light. Schweyk is basically seen to be following a campaign of "opponierendes Mitläufertum" and as such is closely linked with Brecht's most significant political publication "Fünf Schwierigkeiten beim Schreiben der Wahrheit". At the end of the character analysis a definition of Schweyk is formulated based on the qualities of the aforementioned political treatise, so that some observations can be made on the terms "Schweyk figure" and "Schweykian philosophy", both terms which seem to have been abused by the critics. From these observations and the character analysis of Schweyk, it then becomes quite obvious that Schweyk im zweiten weltkrieg is of fundamental importance, since in the character of Schweyk Brecht seems to express his philosophy of life in the clearest, most unequivocal manner.
Keywords: German Language and Literature; German Language and Literature